Potensi Terbentuk Interaksi molekuler pada Fitokimia alami sebagai inhibitor Sap 2 dari Candida albicans: Pendekatan In silico - Gholam, Gusnia Meilin; Artika, I Made (Jurnal Farmasi Udayana; Vol. 11, No. 2, Tahun 2022, 2023)
Candida albicans ( C. albicans ) is a fungus that can live in the digestive tract, mouth, and vagina . C. albicans is the main cause of vulvovaginal candidiasis (VVC), with a percentage of about 80-90%. In addition, C. albicans also causes systemic candidiasis, one of the most common bloodstream infections in hospitalized patients worldwide and is associated with a 40-70% mortality rate. This study aimed to investigate natural phytochemicals potential in inhibiting Sap 2 C. albicans , thereby reducing its virulence factor. The methods used in this study were Sap 2 protein receptor preparation, test ligand preparation, validation and molecular docking of Sap 2, data analysis and visualization, and ADMET prediction using pkCSM. The results of this study are that Silibinin has the closest bond energy to the crystallographic ligands of 8.658 kcal/mol and Apigenin (7.608 kcal/mol), Catechin (7.469 kcal/mol), Resveratrol (6.329 kcal/mol), Gallic acid (5.245 kcal/mol) respectively. Receptors-ligands complex form van der Waals interaction and hydrogen bonds, including hydrogen bond distances. Each test ligand was predicted to bind with the catalytic residues and the S2 S3 and S4 substrate binding pockets from Sap 2. This study concludes that there are molecular interactions of the phytochemicals to inhibit Sap 2.